PENGARUH RASIO TEPUNG KETAN DENGAN TEPUNG LABU KUNING (Cucurbita moschata) TERHADAP KARAKTERISTIK DODOL - Parayana, I Made Adhi Dharma; Suter, I Ketut; Suparthana, I Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2017)
The aims of this research are to determine the effects of ratio sticky rice flour with pumpkin flour on the characteristics of dodol and to find the right ratio between the amount of sticky rice flour and pumpkin flour to produce dodol with the best characteristics. The research design used is randomized block design with ratio between the amount of sticky rice flour and pumpkin flour respectively as follows: 100%: 0%, 85%:15%, 70%:30% , 55%:45%, and 40%:60%. The treatment was repeated three times producing 15 units of the experiment and the data was analysis by variance analysis. If there was impact on the variable, the analysis will be followed by Duncan test. The result of the research showed that ratio between the amount of sticky rice flour and pumpkin flour had significance effects on the content of water, ash, fat, protein, ? -Carotene , IC 50 , colour, aroma, flavor, texture and overall acceptance. The best characteristics of dodol was found on ratio between 40% sticky rice flour and 60% for pumpkin flour with characteristic : water content 10.12%, ash content 4.99%, protein content 6.43%, fat content 13.56%, ? -Carotene 0.0340%, IC 50 37.74% and results of sensoris test color, aroma, taste, texture, and overall acceptance are like.
Keywords: dodol, sticky rice flour, pumpkin flour